Aprovechamiento de lodos de perforación generados por actividad minera en la Parroquia Palo Quemado Provincia Cotopaxi para elaboración de Compost - Ashqui Silva, Andrea Marilin (2018)
The purpose of this research establish to find the appropriate dose to make compost for short cycle cultivation, taking advantage of the drilling muds of mining activity produced by Kluane Drilling Ecuador SA, in the Palo Quemado-Province of Cotopaxi for which it was envisaged to implement a Complete Design Azar (DCA) with a factorial arrangement of treatments (A x B) in mud and poultry mixtures, respectively, with three repetitions per treatment. The results of the objectives initially indicated that the chemical parameters of the mud, such as metals (cadmium and mercury), do not exceed the criteria of Remediation or Restoration according to land use (agricultural, commercial, residential and industrial). It was determined that organic compost can be made from the sludge generated in the exploration phase of the mining company Kluane Drilling Ecuador S.A.